Analisis Dampak Pengumuman Dividen Terhadap Perubahan Harga, Abnormal Return, Dan Volume Perdagangan Saham Sebelum Dan Sesudah Pembagian Dividen Bank Pembangunan Daerah Jawa Timur Tbk Tahun 2015-2017 - Amrulloh Amrulloh; Muhammad Abdul Muis (Kesatuan Press, 2019)
This study aimed to analyze the differences between stock prices, abnormal return and trading volume before and after dividend payout of the Bank Pembangunan Daerah Jawa Timur Tbk. The research methodology used is quantitative method with panel data types (cross section and time series) and the source of data derived from secondary data obtained from the Indonesia Stock Exchange. Mechanical sampling using purposive sampling method with daily data and the study period from 2015 to 2017. The data analysis technique used is the calculation of the share price, abnormal stock returns and trading volume, the study of events from 40 working days before the event, period, and during the 20 working days after the announcement of the dividend payout, as well as two different test average of pairs (t-test) to see the closeness of the relationship between the two variables with a significance level of 5%. The results of this study indicate that the stock price method approach the results obtained there are differences in stock prices before and after dividend payout of Bank Pembangunan Daerah Jawa Timur Tbk period 2015 to 2017. Meanwhile, the abnormal return approach the results obtained there is no difference of abnormal return before and after dividend payout of Bank Pembangunan Daerah Jawa Timur Tbk period 2015 to 2017. Similarly, the volume of stock trading method approach result that there is no difference in the volume of stock trading before and after dividend payout of Bank Pembangunan Daerah Jawa Timur Tbk period 2015 and 2016. But the result in 2017 show that there are differences in trading volume of the stock before and after the dividend payout of Bank Pembangunan daerah jawa Timur Tbk.